Uncertainty Analysis of Vehicle Suspension Systems Based on Polynomial Chaos Methods - Ling Feng; Ma Ze-Yu; Tang Zheng-Fei; Chen Yong-Fu (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
In this paper, a parametrical uncertainty analysis of vehicle suspension system was presented. Four degree-of-freedom(DOF) mathematical model of vehicle passive suspension has been set up and uncertainty of the model has been studied using polynomial chaos methods. By comparing with Monte Carlo simulation method, the results show that polynomial chaos methods are more efficient than Monte Carlo method and are a relatively powerful approach for the simulation of multibody dynamic system with uncertainties.